2002 IEEE International Solid-State Circuits Conference. Digest of Technical Papers (Cat. No.02CH37315)
DOI: 10.1109/isscc.2002.992101
|View full text |Cite
|
Sign up to set email alerts
|

A GSM/GPRS mixed-signal baseband IC

Abstract: A dual-core baseband processor IC for GSM/GPRS cellular phone applications is built in a 0.13pn CMOS process with 5 levels of copper interconnect and contains a high level of mixed-signal integration which includes: 1GHz CMOS synthesizer, 10b general-purpose ADC, two 14b ADCs, power amplifier controller, and 13b voice CODEC. k D. Redmond

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Little work is found in the literature comparing the isolation of rings against that achieved with wells. We will mention [22] where experimental measurements showed that a triple-well technology (two nested wells) on lowresistive bulk provided roughly 20 dB isolation, compared to about 5 dB of a guard ring. Also, in [23] simulation results showed that an isolated p-well (two nested wells) could provide 15 dB of isolation.…”
Section: Isolation With Horizontal Layersmentioning
confidence: 99%
“…Little work is found in the literature comparing the isolation of rings against that achieved with wells. We will mention [22] where experimental measurements showed that a triple-well technology (two nested wells) on lowresistive bulk provided roughly 20 dB isolation, compared to about 5 dB of a guard ring. Also, in [23] simulation results showed that an isolated p-well (two nested wells) could provide 15 dB of isolation.…”
Section: Isolation With Horizontal Layersmentioning
confidence: 99%